Rekonseptualisasi Istilah Desa Kala Patra sebagai Konteks Situasi dan Konteks Tradisi Untuk Mengikat Intensionalitas Meminta Sesuatu dalam Bahasa Bali - I Made Netra (Balai Bahasa Provinsi Bali, 2023)
Language and culture have a reciprocal relationship. Any language in the world adheres to the proposition that language can influence culture and culture can influence language. Therefore, this paper aims to reconceptualize the term of desa kala patra, so that it can function as a context of situation and context of tradition with and without adjustments to bind the intentionality of requesting in Bali language. This research is field research using a qualitative approach. Data was obtained using the participatory observation method using note-taking techniques. Linguistic data in the form of the dictum meaning